Research on the low-temperature performance of basalt fiber- rubber powder modified asphalt mixtures under freeze-thaw in large temperature differences region - Xiaote Shi; Chundi Si; Kewei Yan; Yuefeng Zhu (Scientific Reports)
Abstract Accurately assessing the low-temperature performance of asphalt materials is important for asphalt pavements in cold regions with large temperature differences. This study investigates the effects of freeze-thaw cycles on the low-temperature performance of basalt fiber-rubber powder composite modified asphalt mixtures (BRMAM). The influence of basalt fibers content on the mechanical properties of asphalt binder was characterized through basic property tests and bending beam rheometer (BBR) assessments. A freeze-thaw cycle process was designed to stimulate the more realistic climate. The deterioration of low-temperature performance and freeze-thaw damage mechanism were analyzed by the splitting tensile test, three-point bending test and semi-circular bending (SCB) test. Methods suitable for evaluating BRMAM’s low-temperature performance were compared and explored. The results indicate that when fiber content was about 0.3%, the reinforcement effect of basalt fibers on asphalt material was more pronounced. As freeze-thaw cycles progress, the impact of frost heave force on the cracking resistance significantly increases, while the influence degree gradually decreases. Excess fibers reduced the interfacial bond between rubber powder modified asphalt and aggregate. When fiber content is between 0.2 and 0.4%, BRMAM demonstrates optimal low-temperature performance and the least sensitivity to freeze-thaw cycles. After 30 cycles, the TSR of BRMAM with 0.3% basalt fiber even reached 47.6%.